Back to the binary: How the Olympics struggle with separation of male and female - Boyd, A. (DePaul Journal of Sports Law, 2018)
This comment will examine the legal rights individuals have when changing, altering, or amending their legal classification for sex/gender in the context of the Olympics. Part II will examine the Olympics` historical struggle to determine how gender and sex are verified and classified as well as constitutional issues regarding discrimination and invasion of privacy. Parts III and IV will describe the most recent athlete, Dutee Chand, who challenged the Olympics` hyperandrogenism regulations and her partial success. Part V will briefly examine the commonly proposed options for how the Olympics could split athletes for competition and the legal issues stemming therefrom. The last section of Part V will propose a new approach to athletic classification in the Olympic arena, consider constitutional issues this proposal faces, and explain why hormone ranges remain the best option the Olympics Committee has. This last proposal encompasses a dramatic shift toward the hormone testing of all athletes regardless of sex and rids the Olympics of sex/gender classification, which best combats the constitutional and legal issues surrounding all other options available to the Olympic Games.